2014
DOI: 10.1038/srep07008
|View full text |Cite
|
Sign up to set email alerts
|

RhoA and Membrane Fluidity Mediates the Spatially Polarized Src/FAK Activation in Response to Shear Stress

Abstract: While Src plays crucial roles in shear stress-induced cellular processes, little is known on the spatiotemporal pattern of high shear stress (HSS)-induced Src activation. HSS (65 dyn/cm2) was applied on bovine aortic endothelial cells to visualize the dynamic Src activation at subcellular levels utilizing a membrane-targeted Src biosensor (Kras-Src) based on fluorescence resonance energy transfer (FRET). A polarized Src activation was observed with higher activity at the side facing the flow, which was enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 47 publications
0
47
0
Order By: Relevance
“…These signaling pathways in turn orchestrate a coordinated cellular response resulting in reorganization of the actin cytoskeleton, redistribution of intracellular tension, and a shift in phosphorylation of VE-cadherin and associated catenins 142, 167169 . Using a recently developed biosensor that measures actomyosin-mediated tension across VE-cadherin adhesion and PECAM-1, it was shown that shear stress applied to an endothelial monolayer reduces tension across VE-cadherin adhesion concomitant with a decrease in total cell-cell force 142, 170 . Thus, it appears that the distribution of intracellular tension is tightly regulated in response to external mechanical forces thus allowing AJs to align in the direction of flow.…”
Section: Mechanisms Of Ve-cadherin Cis- and Trans-interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…These signaling pathways in turn orchestrate a coordinated cellular response resulting in reorganization of the actin cytoskeleton, redistribution of intracellular tension, and a shift in phosphorylation of VE-cadherin and associated catenins 142, 167169 . Using a recently developed biosensor that measures actomyosin-mediated tension across VE-cadherin adhesion and PECAM-1, it was shown that shear stress applied to an endothelial monolayer reduces tension across VE-cadherin adhesion concomitant with a decrease in total cell-cell force 142, 170 . Thus, it appears that the distribution of intracellular tension is tightly regulated in response to external mechanical forces thus allowing AJs to align in the direction of flow.…”
Section: Mechanisms Of Ve-cadherin Cis- and Trans-interactionmentioning
confidence: 99%
“…This is evident by the finding that they induce differential phosphorylation of VE-cadherin and p120-catenin 165, 166, 188190 . Some mediators, such as thrombin, function through phosphorylating VE-cadherin at Tyr 658 by c-Src 170, 172 or p120 catenin at Ser879 by protein kinase C (PKC)α resulting in decreased binding of VE-cadherin to p120-catenin 185, 189 . Indeed, leakage of tumor vessels is associated with c-Src-dependent phosphorylation of VE-cadherin and β- and p120-catenin proteins 191 .…”
Section: Signaling Mechanisms Mediating Stability and Remodeling Omentioning
confidence: 99%
“…One study has reported that Src plays crucial roles in shear stress-induced cellular processes [23]. A report published by Hum et al revealed that mechanical loading may induce the formation of a Src/Pyk2/MBD2 complex in the nucleus, that functions to suppress anabolic gene expression [24].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, subcellular ATP FRET-biosensors are used to visualize intracellular energy transport following inhibition of glycolysis (7), while oxygen FRET-based biosensors can monitor intracellular oxygen transport and consumption (8). Wang and colleagues have developed a simultaneous multi-parametric analysis of distinct FRET biosensors including Src, RhoA and FAK and, thereby, demonstrated their interdependent regulation in response to mechanoreciprocity, which is known to drive tissue dysplasia and metastasis in a variety of cancers (9,10). In addition, the development of Raichu Rho GTPase FRET-biosensors has significantly improved the understanding of actomyosin cytoskeletal remodeling, cell proliferation and motility in cancer (11).…”
Section: Discussionmentioning
confidence: 99%